PENGEMBANGAN LEMBAR KEGIATAN SISWA BERBASIS GUIDED DISCOVERY PADA MATERI BANGUN RUANG SISI DATAR SISWA KELAS VIII SMP NEGERI 14 SURAKARTA - Maharani, Kartika; Ratri, Dyah; Ekana, Henny (Universitas Sebelas Maret, 2018)
Abstract: The research aims to describe the development procedure of Student Activity Sheets (SAS) using Guided Discovery and to obtain a valid, attractive, efficient, and effective Student Activity Sheets to Improve Students’ Learning Outcomes. The research population is all of the eighth grade students in Junior High School 14 Surakarta. Two classes used as the samples are VIII A and VIII B through cluster random sampling. The type of this research is a Research and Development (R & D). The development procedure of this research is based on ADDIE (Analyse, Design, Development, Implementation, and Evaluation) Development Model. The scoring result from the material experts reach the average score of 3.36 in the level ‘good’ and the scoring result from the design experts reach the average score of 3.25 in the level ‘good’. Therefore, the data shows that the SAS is considered to be valid. The result from the student questionnaire responses reach the average score of 3.56 in the level ‘very good’. Therefore, it can be concluded that the SAS is attractive. Meanwhile, the scoring result from the teacher questionnaire responses reach the average score of 3.4 in the level ‘good’. Therefore, it can bee seen that the SAS is considered to be efficient. To see the effectiveness of SAS conducted t-test and from the average test result with t test, t = 1,9881 is a member of DK = t | t> 1,645. This means that the value of the students' learning outcomes in the experimental class is better than the control class, so that it can be concluded that the SAS effectively improves student learning outcomes. From this result, it can be concluded that Student Activity Sheets of Polyhedron Material using Guided Discovery is considered to be valid, attractive, efficient, and effective.Keyword: pengembangan, LKS, penemuan terbimbing, geometri